The Effect of Different pH in Extraction Process Against Physicochemical Properties of Refined Iota Carrageenan from Eucheuma spinosum Seaweed. - Miftakhul Ulumiah; Mochammad Amin Alamsjah; Kustiawan Tri Pursetyo (Journal of Marine and Coastal Science, 2019)
Gelatin is a simple protein obtained from the partial hydrolysis of collagen from the skin, bones, joints and connective tissue of animals. One potential material for the manufacture of gelatin is fish bone milkfish (Chanos chanos). Gelatin derived from fish bones with acid process is able to change the triple helix collagen fibers into a single chain, whereas the solvent base only produce double chain. Demineralization of bone or fish skin should use a weak acid is acetic acid, because when using strong acids will produce a strong scent and color gelatin becomes dark. This study aims to determine the effect of the use of acetic acid to the production of fish bone gelatin and the concentration of acetic acid is necessary to produce gelatin with physical and chemical properties of the best. This study uses a Completely Randomized Design (CRD) with four treatments and five replications. The treatments used in this study is the concentration of acetic acid 2%, 4%, 6% and 8%. Based on the research, it was found that the acetic acid solvent effect on the value of the yield and gel strength, but has no effect on the pH value and viscosity. Acetic acid concentration 8% give 4.102% yield value; pH value (acidity) 4.98; 134.313 bloom gel strength and viscosity of 3.6 cP. FTIR analysis results indicate that the fish bone gelatin produced from this research have the same functional group with commercial gelatin.